Development of a national human resource development conceptual model as practiced in Malaysia - Devadas, Udaya Mohan (2012)
National Human Resource Development (NHRD) is an important national policy agenda in many countries and has been an emerging research agenda. In contributing to it, this study described and articulated the nature of NHRD practices within Malaysia eventually aggregating this understanding into a conceptual model. The literature review of this study demarcated traditional HRD and modern HRD while placing NHRD as a modern and macro HRD showing its plausibility to resolve contemporary HRD challenges in the face of achieving national development. A qualitative approach, designed as a case study method using Straussian grounded theory was adopted. The overarching research question of this study was ‘which conceptual model will facilitate, as common knowledge, to describe and understand the nature of NHRD within Malaysia?’ This was assisted by three sub research questions to study separately the pressures and imperatives of NHRD; NHRD initiatives, their outcomes, and the characteristics; and the facilitating and resisting forces of NHRD’s implementation. Data were gathered from the Ninth and the Tenth Malaysia Plans and from 19 interviews held at 11 relevant ministries. In resolving the overarching research question, the study constructed a conceptual model depicting the pressures and imperatives that pull NHRD at its planning level, the enabling and hindering forces that influence in and the challenges that are confronted with NHRD plan implementation, as well as the NHRD outcomes resulted in the achievement of national goals in resolving Malaysia’s national challenges. It was found that Human Capital and Talent Development (HCTD) represents NHRD within Malaysia to supply the needed human capital in order to cater to the economic development needs aiming at achieving the country’s long term goal—vision 2020. This HCTD is highly influenced by the global environment conditions through Malaysia’s economic conditions. However, the government plays a key role cushioning the Malaysia’s domestic economy against the global environment pressures to fortify the economic activities and country’s socio-cultural conditions through its strong leadership and proactive national planning. At its implementation, NHRD has been facilitated, hindered and challenged by the factors from the areas pertaining to government, resources, cooperation, and socio-cultural context. The understanding obtained regarding Malaysia’s NHRD is useful to the practitioners in their national policy decisions and determining the needed interventions in implementing them. Importantly, this study contributes to the development of NHRD theory in terms of new knowledge generated on Malaysia’s NHRD and the methodological insights employed in deriving such knowledge.